A model for marriage covenant, grace, empowerment and intimacy - Balswick, Jack O.; Balswick, Judith K. (Downers Grove, Ill. : IVP Academic, 2006)
Jack and Judy Balswick offer a vision of marriage that is both profoundly spiritual and thoroughly practical. Drawing insight from Christian theology and from social science research, the Balswicks bring together their years of teaching, writing and being married to each other to produce a book of faith and wisdom for facing the challenge of marriage in the twenty-first century.
The dilemma of modern marriage -- A trinitarian model of marriage -- Covenant marriage : the greatest of these is love -- The gracing marriage : grace-full love -- The empowering marriage: mutual empowerment and mutual servanthood -- The intimate marriage: knowing and being known -- Leaving, cleaving and becoming one flesh -- Differentiated unity -- Communication, connection, communion -- Conflict : the fertilizer of growth -- The seasons of marriage -- The dual-earner marriage : an elaborate balancing act -- Sexuality in its splendor : one-flesh mystery -- Marital spirituality.
Includes bibliographical references (p. [194]-206) and indexes.
Description based on print version record.
Keywords: Marriage -- Religious aspects -- Christianity; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books